Diseño de un sistema de iluminación con energía solar fotovoltaica para la universidad Antonio Nariño sede Cúcuta (2021)
The objective of this research work is to design a photovoltaic lighting system for the Antonio Nariño University of the Cúcuta headquarters, which seeks to benefit the users of the aforementioned university and the institution as such, because it would improve the provision of services to the user and at the same time it would reduce the expenses for the concept of electric power service; It will be developed under a feasible project with a descriptive design, with a documentary review of all the material referring to the photovoltaic system and its different components. As a result, it seeks to design the lighting system through photovoltaic cells to improve the lighting of the university, reducing the costs of this type of service, thereby increasing the quality of service for users of this important educational institution, for this the number of investors, panels, regulators necessary for its execution will be determined.